Ecotourism Research Evolution in Southeast Asia: Key Trends and Future Directions - Rendy Rendy; Vieronica Varbi Sununianti; Iwano Junna; Adha Akasyah Bin Abd Razak (Yayasan Keluarga Guru Mandiri, 2026)
Publications on ecotourism in Southeast Asia over the past decade have shown significant development. This article aims to map the dynamics of those publications through a bibliometric study of 377 documents from the Scopus and Web of Science databases since 2014 to 2024. Data processing used Bibliometrix and VOSviewer software. The findings show publication dominance by Thailand through Srinakharinwirot University. International collaboration networks are led by the University of Göttingen and the University of Tartu. Publication sources on sustainable tourism are distributed across a number of globally reputable journals in various disciplines. The findings show that ecotourism studies are not limited to conservation. Based on the thematic review, research directions have shifted toward biodiversity conservation, strengthening sustainable tourism frameworks, and inclusive economic approaches for local community well-being. This study highlights the importance of integrating cross-cutting ecological and socioeconomic perspectives in ecotourism development and opens space for more contextual and applied academic exploration.